Identity, meaning, and subjectivity in career development : evolving perspectives in human resources - Gedro, Julie, 1962- (Springer International Publishing : Imprint : Palgrave Macmillan, 2017)
This book closely interrogates the construct of identity and the role it plays in career development. It provides guidance for HRD practitioners and researchers who create career development programs through a typology of different categories of identity, such as demographics, life events, and career histories. The book presents a framework for considering and addressing career development from a critically reflective perspective of identity as a result of choice, chance, and adaptation. It offers a comprehensive understanding and awareness of tacit, nuanced, and stigmatized issues that were once shameful but have now become more socially acceptable. As a result, HRD practitioners can design programs and resources that have a richness and relevance that might heretofore be lacking. The book also offers guidance for individuals as they take charge of their own identities and career trajectories in an increasingly complex and unpredictable working environment.
Keywords: Career development.; Business.; Leadership.; Personnel management.; Self.; Identity (Psychology); elektronické knihy; electronic books